Bezpieczeństwo jako podstawowy element realizacji utopii edukacyjnych XIX i XX wieku - Futyma, Sławomir (Kultura-Społeczeństwo-Edukacja, 2016)
This reflection is associated with unquestionable power of utopia in education. Education has always been associated with the implementation of social utopia. The intensity of this activity can be observed especially in the nineteenth and twentieth centuries. With utopia, education systems may take into account future scenarios, risk, and to disseminate the truth that knowledge and early solution to the problems is a prerequisite for social security.